The ADHD brain and learning - Barasuol , Fabiana Fagundes (Seven Editora, 2024)
The brain is the most complex organ in the human being. It is responsible for our thinking, attention, memory and learning. A series of higher functions and neuronal circuits enable learning to take place. A person with Attention Deficit/Hyperactivity Disorder (ADHD) has a series of problems in managing their behavior, such as difficulties in maintaining their attention, controlling and inhibiting impulses and excessive activity, impairing their learning. In most cases, it is in the school environment that the symptoms of this disorder are most clearly seen. A combination of educational strategies, emotional support and adaptive interventions can be essential to optimize the learning process and promote academic and personal success. DOI:https://doi.org/10.56238/sevened2024.001-008